COMPARISON OF DURATION PLAYING DEFENSE OF THE ANCIENTS-2 VIDEO GAME WITH REACTION TIME - Yosua Arif Hadi; Yuswo Supatmo; Novi Kusumaningrum; Hardono Susanto (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Background: DotA-2 is the most popular MOBA video game, which ranks the second most sold on the steam platform. Reaction time as a physiological parameter to find out how quickly to respond to a stimulus. Some research states that video games can increase reaction time. Objective: To know the correlation of playing video game Defense of the Ancients-2 with the duration of reaction time. Method: The study used cross-sectional design. This study was conducted in the area of the Faculty of Medicine, Diponegoro University. In this study found 42 respondents participated. Score of reaction time is measured using a ruler dropped from the respondent's fingertips. Analysis using Shapiro-Wilk test and Pearson test. Results: There is significant relationship between playing a DotA-2 status and reaction time. The duration of playing DotA-2 video games to the reaction time there were significant differences between the 3 groups. Conclusion: There is a significant relationship between the status of playing video game DotA-2 with reaction time.